Wind-driven upwelling on the Western Agulhas Bank: a study using ERA5 and WASA3 winds - Birkett, Giovanna (Department of Oceanography, 2024)
The Southern Benguela Upwelling System (SBUS), located along the west coast of South Africa, is unique in that it is the only eastern boundary upwelling system bounded at both ends by warm water masses, and with no continental boundary between it and the adjacent western boundary current, the Agulhas Current. The Western Agulhas Bank (WAB), defined as the region over the Agulhas Bank from Cape Point to Cape Agulhas, is the southernmost region of the SBUS however it has a markedly different coastline orientation, and upwelling dynamics in this region are understudied. This study compares two different modelled wind products, ERA5 (31 km resolution) and WASA3 (3.33 km resolution), assessing coastal winddriven upwelling in the WAB. Wind-driven upwelling, derived from the higher resolution WASA3 dataset is used to identify and investigate the seasonality of three discrete regions of upwelling within the WAB. WASA3 is shown to capture stronger orography-induced wind stress curl which drives the locations of upwelling cells and contributes 67.23% to the total upwelling velocity observed at Cape Hangklip in January, just more than double the contribution of alongshore wind stress driven Ekman pumping. Theoretical wind-driven upwelling in Cape Hangklip is shown to be stronger than in the Cape Peninsula upwelling cell in January, despite previous literature describing the Cape Peninsula as a stronger upwelling cell. This indicates that other factors not accounted for in this study likely suppress upwelling at Cape Hangklip, such as shallow bathymetry and stratification. The study highlights the importance of using a high-resolution wind product to resolve small scale features, emphasising that numerical models using low resolution wind products such as ERA5 should be used with caution when interpreting simulated upwelling velocities. Given the socioeconomic importance of the WAB, and the effect of the upwelling on aquaculture, fishing and tourism in this region, it is suggested that WASA3 or a similar high resolution wind dataset is used to force numerical models with the aim of gaining a greater understanding of the upwelling dynamics in this region.